KOtBu-promoted C3-homocoupling of quinoxalinones through single electron transfer from an sp2 carbanion intermediate. Issue 50 (6th June 2022) - Kwon, Na Yeon; Mishra, Neeraj Kumar; Park, Jung Su; Woo, Sang Kook; Ghosh, Prithwish; Kim, In Su
Abstract : An efficient protocol for the C3-homocoupling reaction of quinoxalinones with potassium tert -butoxide is described. The detailed mechanistic pathway on the single electron transfer (SET) process has been proposed. Abstract : The C3-selective homodimerization of quinoxalinones is described. A C3-sp 2 carbanion species generated through deprotonation of quinoxalinone using potassium tert -butoxide (KO t Bu) transfers an electron (single electron transfer mechanism) to a second quinoxalinone, affording a radical–anion intermediate. The radical scavenging and electron paramagnetic resonance (EPR) experiments support the plausible radical reaction pathway. A mild reaction temperature and a short reaction time were attained under cost-effective conditions, which reveal the amenability of this protocol to pharmaceutical and chemical industries.